2015
DOI: 10.1002/ejic.201403176
|View full text |Cite
|
Sign up to set email alerts
|

Suzuki Coupling Reactions Catalyzed with Palladacycles and Palladium(II) Complexes of 2‐Thiophenemethylamine‐Based Schiff Bases: Examples of Divergent Pathways for the Same Ligand

Abstract: Activation of Suzuki coupling with a complex of palladium varies with the mode of coordination of its ligand. The moisture‐/air‐insensitive palladacycles and palladium complexes designed using the same ligand (Schiff base, coordinating as an N,C– and N,O– ligand, respectively) have been found to follow different pathways. Palladacycles are more efficient, as their 0.001 mol‐% loading gives good conversion (yield > 90 %) in several cases. Higher loading than this is required for Pd complexes to obtain a similar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(11 citation statements)
references
References 51 publications
1
8
0
2
Order By: Relevance
“…Pd–N (quinoline nitrogen) bond lengths are 2.014(2), 2.123(3), and 2.102(4) Å, respectively, consistent with reported neutral Pd–N bond lengths (2.005–2.035(3) Å) . The Pd–C bond distances in C2 and C3 are 1.998(4) and 1.983(5) Å, respectively, which are similar to the value 1.979(4) Å reported earlier for a palladacycle complex Figure and Figure s1 show the unit cell representations of C1 – C3 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Pd–N (quinoline nitrogen) bond lengths are 2.014(2), 2.123(3), and 2.102(4) Å, respectively, consistent with reported neutral Pd–N bond lengths (2.005–2.035(3) Å) . The Pd–C bond distances in C2 and C3 are 1.998(4) and 1.983(5) Å, respectively, which are similar to the value 1.979(4) Å reported earlier for a palladacycle complex Figure and Figure s1 show the unit cell representations of C1 – C3 .…”
Section: Resultsmentioning
confidence: 99%
“…28 The Pd−C bond distances in C2 and C3 are 1.998(4) and 1.983(5) Å, respectively, which are similar to the value 1.979(4) Å reported earlier for a palladacycle complex. 29 Figure 4 and Figure s1 show the unit cell representations of C1−C3. Complex C1 contains four molecules in its unit cell, but we have not observed any solvent molecules in the unit cell, whereas complex C2 has four molecules in its unit cell with four solvated CHCl 3 molecules and complex C3 has only two molecules in its unit cell with two solvent molecules.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…In Vicente's research, 14c,d this conclusion was unambiguously confirmed by a rich set of additional testing experiments and ESI-MS detection of two palladium(IV) intermediates in the catalytic process. The opposite assumption about the homogeneous Pd(II)/Pd(0) pathway has been made in other reports 15,16 after a negative mercury drop test was obtained, despite the lack of an induction period in the kinetic curve 16 and the opportunity to regenerate and reuse the catalyst. 16a,b Although the formation of strongly protected soluble palladium(0) species was not proven, it may be assumed in systems with C,P-or P,C,P-CPCs used as a (pre)catalyst.…”
Section: ■ Introductionmentioning
confidence: 99%
“…The rare exception is the research of Singh's team, who not only confirmed C,N(S)-palladacycle thermal decomposition under catalysis conditions and isolated and characterized in detail the nanoparticles (NPs) formed with Pd 7 S stoichiometry but also established their homogeneous catalytic activity provided by palladium(0) atom leaching. 15 More serious problems arise in the case of a positive mercury test. It was shown that mercury(0) suppresses (completely or partially) 20 the catalytic activity in cross-coupling reactions of palladium(II) cyclometalated C,N-, 20c,21 C,P-, 22 and C,Scomplexes 23 and P,C,P-, 2b,7b,20a,b,24 S,C,S-, 7a,9b, 25 Se,C,Se-, 26 and C,N,E (E = S, Se, Te)-pincers.…”
Section: ■ Introductionmentioning
confidence: 99%
“…The nature of these species in solution is still a debate, as it is also in the case of homogeneous precursors. Some believe that nanoparticles in solution are inevitably formed and are only responsible for the catalytic activity [15], other think that a true homogeneous (complex-catalyzed) mechanism can occur [16]. Apart from that debate, some authors support the idea of real heterogeneous catalysts that do not release any (or sufficient) traces of Pd to contribute to the catalytic activity [17,18].…”
Section: Introductionmentioning
confidence: 99%